(untitled) (Transport systems and technologies, 2023)
This article explores current trends and prospects in passenger cruise ship chartering. In light of events in recent years, including the global COVID-19 pandemic, the cruise industry has faced serious challenges, prompting companies to look for new approaches to support their operations. The article examines different chartering models, including long-term and short-term agreements, as well as the possibility of sharing vessels between operators. Two organizational and legal forms of operation of marine passenger ships are considered in more detail: liner and cruise. Formalized and provided a schematic representation of the process of interaction of the participants of sea passenger transportation in various forms of ship operation. The interaction schemes of the shipowner, the charterer and the managing agent are described. The interaction technology of the participants in the passenger transportation process is considered in the context of the types of ship charter contracts. Differences in technological processes of interaction of participants in the process of organization and provision of sea passenger transportation, distribution of responsibilities, risks, costs and income in the organization of sea passenger transportation according to various schemes of interaction of participants are given.